The Role of Toll-Like Receptor in Inflammation and Tumor Immunity - Cen, Xiaohong; Liu, Shuwen; Cheng, Kui (Frontiers in Pharmacology, 2018)
Toll-like receptors (TLRs) activation enables host to recognize a large number of pathogen-associated molecule patterns (PAMPs), ignite immune cells to discriminate between self and non-self, and then promote the following innate and adaptive immune responses. Accumulated clinical/preclinical evidences have proven TLRs to be critical role in the autoimmune diseases, including inflammatory and tumor-associated diseases. Activation of TLRs is becoming or has been a target for cancer treatment. It is shown that TLRs can induce preferable anti-tumor effect by eliciting inflammatory cytokines expression and cytotoxic T lymphocytes (CTLs) response. As adjuvant, TLRs agonists can launch a strong immune response to assist cancer radiotherapy and bio-chemotherapy. On the other hand, tumor-associated antigens acting as PAMPs, can also activate TLRs and induce tumor gene-related programmed cell death, including apoptosis, autophagy and programmed necrosis. While there are also arguments that the excessive TLRs expression will promote tumor deterioration in various organisms, as the TLR-induced inflammation will accelerate the cancer cells boost in the tumor microenvironment (TME). However, the effect of TLRs acting on cancers is still not quite clear today. In this review, we will summarize the recent researches of TLRs in cancer treatment and their role in TME, giving a brief overview on future expectation.